2019
DOI: 10.1038/s41409-019-0731-x
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib in refractory acute and chronic graft-versus-host disease: a multicenter survey study

Abstract: Graft-versus-host disease is the main cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation. First-line treatment is based on the use of high doses of corticosteroids. Unfortunately, second-line treatment for both acute and chronic graft-versus-host disease, remains a challenge. Ruxolitinib has been shown as an effective and safe treatment option for these patients. Seventy-nine patients received ruxolitinib and were evaluated in this retrospective and multicenter study. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 31 publications
(39 reference statements)
3
40
1
1
Order By: Relevance
“…61 Additional reports continue to support the use of ruxolitinib in this setting of steroid-refractory acute GVHD in adult and pediatric populations. 62,63 The most recent data published includes REACH2 (clinicaltrials.gov; NCT02913261), a phase III randomized, openlabel trial evaluating the efficacy of ruxolitinib 10 mg twice/day compared with best available therapy (BAT) for steroid-refractory acute GVHD. Day 28 overall responses were improved in the ruxolitinib group (62%) compared with the BAT group (39%, p < 0.001).…”
Section: Treatmentmentioning
confidence: 99%
“…61 Additional reports continue to support the use of ruxolitinib in this setting of steroid-refractory acute GVHD in adult and pediatric populations. 62,63 The most recent data published includes REACH2 (clinicaltrials.gov; NCT02913261), a phase III randomized, openlabel trial evaluating the efficacy of ruxolitinib 10 mg twice/day compared with best available therapy (BAT) for steroid-refractory acute GVHD. Day 28 overall responses were improved in the ruxolitinib group (62%) compared with the BAT group (39%, p < 0.001).…”
Section: Treatmentmentioning
confidence: 99%
“…Cytogenetic analysis showed a normal female karyotype. The patient developed a steroid‐refractory gastrointestinal graft‐ versus ‐host disease (Grade 2), which was treated with ruxolitinib and extra‐corporeal photopheresis and controlled 12 …”
Section: Figurementioning
confidence: 99%
“…16 Whilst ruxolitinib was approved by the United States (US) Food and Drug Administration (FDA) for steroid-refractory aGvHD in May 2019, 17 standardised recommendations on how to best implement such a diverse array of treatments remain lacking. 18 The objective of this study was to review and describe reported harm outcomes associated with second- and third-line therapies for GvHD following allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%